Strategi guru Pendidikan Agama Islam dalam meningkatkan kemampuan membaca Al-Qur'an siswa SMP - Susmiyati; Suroso; Haryadi; Habiburrahman, Sayid (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This study examines Islamic Education teachers' strategies in overcoming difficulties in reading the Qur'an at SMP Negeri 1 Babat Toman, Musi Banyuasin Regency a school located in a disadvantaged, frontier, and outermost (3T) region with limited resources. Employing a qualitative case study approach, data were collected through participatory observation (10 sessions), in-depth interviews with the principal, Islamic Education teacher, and three students, as well as documentation. The findings reveal three main themes. First, students' difficulties are multidimensional: technical (makharijul huruf, basic tajwid, reading fluency) and psychological (shyness, fear of mistakes, academic anxiety), exacerbated by minimal prior Qur'anic education experience (>60% of students never attended TPQ) and lack of family support. Second, the teacher developed adaptive-differentiated strategies: grouping students based on initial ability levels, talaqqi method for personalized correction, peer tutoring, audio murottal media and interactive letter cards, as well as joyful learning approaches. Third, strategy effectiveness was supported by teacher commitment, creativity, and school support; yet hindered by time constraints, an unfavorable teacher-student ratio (1:546), lack of specific qira'ah training, and low parental involvement. Contextual and collaborative strategies proved effective in improving students' reading ability and self-confidence despite limitations. This study recommends strengthening teacher capacity, developing contextual learning media, and multi-stakeholder synergy for program sustainability. Abstrak Penelitian ini mengkaji strategi guru Pendidikan Agama Islam dalam mengatasi kesulitan membaca Al-Qur'an di SMP Negeri 1 Babat Toman, Kabupaten Musi Banyuasin sekolah di wilayah 3T dengan keterbatasan sumber daya. Menggunakan pendekatan kualitatif studi kasus, data dikumpulkan melalui observasi partisipatif (10 pertemuan), wawancara mendalam dengan kepala sekolah, guru PAI, dan tiga siswa, serta dokumentasi. Hasil penelitian menunjukkan tiga temuan utama. Pertama, kesulitan siswa bersifat multidimensi: teknis (makharijul huruf, tajwid dasar, kelancaran tartil) dan psikologis (rasa malu, takut salah, kecemasan akademik), diperparah oleh minimnya pengalaman belajar TPQ (>60% siswa) dan dukungan keluarga. Kedua, guru mengembangkan strategi adaptif-berdiferensiasi: pengelompokan berdasarkan kemampuan awal, metode talaqqi untuk koreksi personal, tutor sebaya, media audio murottal dan kartu huruf interaktif, serta pendekatan pembelajaran menyenangkan. Ketiga, efektivitas strategi didukung komitmen guru, kreativitas, dan dukungan sekolah; namun terhambat oleh keterbatasan waktu, rasio guru-siswa tidak ideal (1:546), minimnya pelatihan qira'ah, dan rendahnya keterlibatan orang tua. Strategi kontekstual dan kolaboratif terbukti efektif meningkatkan kemampuan membaca dan kepercayaan diri siswa meski dalam keterbatasan. Penelitian ini merekomendasikan penguatan kapasitas guru, pengembangan media kontekstual, dan sinergi multi pihak untuk keberlanjutan program.